Inflammatory markers in prostate cancer: potential roles in risk stratification and immune profiling - Edgaras Burzinskis; Ieva Janulaityte; Mindaugas Jievaltas; Darijus Skaudickas; Guoda Burzinskiene; Edvinas Dainius; Albinas Naudziunas; Astra Vitkauskiene (Journal of Immunotoxicology)
Inflammation plays a critical role in prostate cancer (PCa) pathophysiology, yet the diagnostic value of specific inflammatory markers remains unclear. This study evaluates the association between circulating and tissue inflammatory markers with PCa presence and their potential as biomarkers for risk stratification. This prospective study analyzed serum and prostate biopsy samples from 60 patients with PCa and 22 cancer-free controls. Concentrations of inflammatory markers, including IL-2, IL-4, IL-10, IL-13, IL-33, Oncostatin M, TNFα, PDGF-BB, and TREM-1, were measured using Luminex technology. Statistical analyses included the Mann-Whitney test, logistic regression, and ROC curve analysis to assess differences and diagnostic performance. PCa patients exhibited significantly higher serum levels of IL-2 (p = 0.001), IL-10 (p < 0.001), IL-33 (p < 0.001), Oncostatin M (p = 0.018), and TNFα (p = 0.017) compared to controls. In contrast, biopsy tissue levels of IL-4 (p < 0.001), IL-10 (p < 0.001), IL-13 (p = 0.004), Oncostatin M (p = 0.012), PDGF-BB (p = 0.039), and TREM-1 (p = 0.013) were significantly lower in PCa patients, suggesting an inverse association. IL-10 (inverse) and IL-4 (inverse) in biopsy tissue showed high specificity in ROC analysis (AUC = 0.788 and 0.804, respectively), while IL-2 and IL-33 in serum were positively associated with PCa risk. This study suggests that IL-4, IL-10, and IL-13 in biopsy tissue may serve as biomarkers of a protective effect, while elevated IL-2 and IL-33 in serum are associated with an increased risk of PCa. These findings highlight the potential of inflammatory markers in PCa risk stratification, warranting further investigation in larger cohorts.